2016
DOI: 10.1002/pbc.26036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Symptomatic and Asymptomatic Thrombosis in Pediatric Oncology Patients With Tunneled Central Venous Catheters

Abstract: Prevalence of both symptomatic VTE and asymptomatic CVC-related VTE was low compared to other studies, which may be explained by the inclusion of patients with solid tumors, reduction of CABSI by ethanol, use of tunneled CVCs, and use of US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 24 publications
(74 reference statements)
4
26
0
Order By: Relevance
“…CVC is the most common risk factor for VTE in children with cancer. Reported rates of symptomatic catheter-related VTE range from 2.6 to 36.7%, and rates of asymptomatic catheter-related VTE range from 5.9 to 43% ( 25 27 ).…”
Section: Venous Thromboembolism In Children With Cancermentioning
confidence: 99%
“…CVC is the most common risk factor for VTE in children with cancer. Reported rates of symptomatic catheter-related VTE range from 2.6 to 36.7%, and rates of asymptomatic catheter-related VTE range from 5.9 to 43% ( 25 27 ).…”
Section: Venous Thromboembolism In Children With Cancermentioning
confidence: 99%
“…Previous studies have reported a TE incidence of between 2.1 and 16% for symptomatic events in children with cancer, and up to 40% when accounting for asymptomatic events. [7][8][9][10][11][12][13][14][15][16][17][18] Several risk factors have been proposed for TE in children with cancer. Previously described patient-specific factors include older age, higher body mass index (BMI), presence of thrombophilia and non-O blood group.…”
Section: Introductionmentioning
confidence: 99%
“…22 Published data in children are mostly limited to singlecentre, single disease retrospective studies or prospective studies consisting of children with acute lymphoblastic leukaemia (ALL). 7,8,11,[13][14][15][16][17][18][19][22][23][24][25][26][27] A large multi-institutional study that includes all paediatric cancer types is important to improve our understanding of risk factors for TE, and to have a sufficiently large sample size allowing for robust modelling and improved precision in estimates. Therefore, our objectives were to describe the incidence of thrombosis and to identify risk factors for thrombosis among Canadian cancer patients less than 15 years of age using a population-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively short follow-up periods of included studies carry a risk of underestimation of the effectiveness of thromboprophylaxis (and conversely, overestimation of its safety), as TE or bleeding events could be missed both in the intervention and control groups. Yet, current evidence states that TE occurs early on following diagnosis and treatment of ALL in children, 38 leading us to believe that the majority of TE would be captured despite the short follow-up period of some studies. Third, a high degree of heterogeneity was observed among study findings suggesting inconsistencies in effect size for effectiveness of thromboprophylaxis modalities across trials for reasons that are not immediately apparent on qualitative assessment of the studies.…”
Section: Standard Of Carementioning
confidence: 99%